PRODUCT LIFE CYCLE MANAGEMENT AS A KEY FACTOR OF “GREEN” MANAGEMENT IN THE CONSTRUCTION INDUSTRY - Abdullaev, Nokisbay (International Conference on Business & Management, 2026)
In the modern economy, the competitiveness of industrial enterprises is determined not only by production volume, but also by their environmental responsibility and resource efficiency. Although the concept of “green” management is interpreted differently in economic literature, it is fundamentally based on the synergy between economic benefit and environmental sustainability.